IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM PEMBENTUKAN KARAKTER ISLAMI ANAK DI TK IT AL-HIKMAH - Imaniar, Mahrati; Roswati, Roswati; Yakin, Nur Rahayul; Hartini, Yuhandi; Anggryani, I'in (TARBAWI:Journal on Islamic Education, 2025)
concepts to children is religious education for children. Religious education is given from an early age. A simple example of introducing religious values to children is that nature is God's creation, so it can be applied by observing plants, animals, mountains, earth and others that adhere to Islamic teachings. Then the organization teaches learning activities, namely Worship, especially prayer, ablution, reciting the Koran and practicing it in an Islamic way to teach morals to children. Based on this description, this study aims to determine the application of Islamic religious education in early childhood in shaping children's character. This study uses descriptive qualitative research, where this study discusses policies, concepts and theories.               Methods and information from the results of data collection related to the concept of Islamic religious education (PAI) learning. Establishing Islamic Religious Education (PAI) in early childhood is one way to teach Islamic religious values to children. Instilling Islamic religious values from an early age means instilling good character in children. In TK IT Al-Hikmah as an integrated Islamic institution, there are many activities that serve as references to support Islamic Religious Education learning in the institution, such as the Iqro class where children are specifically guided to be able to recite the Koran, memorize short verses or even Juz 30, hadiths, daily prayers, and prayer practices which are carried out routinely every day.